The marginal literature and the tradition of literature: Ferréz’s manifest-preface, “Literary Terrorism” - Luciano Barbosa Justino (Gragoatá, 2007)
This paper aims to investigate the “Literacy terrorism” in Ferréz’s manifest-preface as the side literature related to a strong domain sense on the part of those who write from a certain position – the slum dweller in a big brazilian city who creates a new literature rule and sets a particular style to deal with the literacy tradicion.